Weibliche Herrschaft im 18. Jahrhundert : Maria Theresia und Katharina die Große - Braun, Bettina; Kusber, Jan; Schnettger, Matthias (Mainzer Historische Kulturwissenschaften, 2020)
In Maria Theresa and Catherine the Great, the volume compares two of the most important rulers of the 18th century and shows how they met the special challenges they faced as ruling women.